Bioprospecção de fungos filamentosos para produção de proteases utilizando leite desnatado como substrato - Silva, Geisi Maria Henrique da (2019)
Filamentous fungi are highly relevant organisms in the production of bioactives. An example of bioactive compounds are enzymes, such as proteases, involved in important metabolic changes, which stand out in their use in industrial processes in several areas. However, the need to search for enzymes with more attractive characteristics for the industry and with low production cost is increasingly seen. In view of this, the present work aimed at the bioprospecting of filamentous fungi for the production of protease by submerged fermentation using skimmed milk with inducing substrate. Fungal isolates from zebrafish eggs were subjected to macroscopic (growth in Petri dish) and microscopic (cover slip culture) analysis, and the potential for proteolytic production in solid agar-milk medium, which proved to belong to the genera Penicillium sp. and Clonostahcys sp. and show positive protease activity. The isolates of Beauveria brongniartii and Paecilomyces sp., Were previously analyzed. For the production of protease, 0.5 ml of conidia suspension (1x109 conidia / ml) was inoculated in 50 ml of skimmed milk (5%), for 5 days at 180 rpm, RT. Proteolytic activity was determined using the azocazein and tricloacetic acid (TCA) method. The crude extracts from the fermentation processes showed activities of 1.3 U / mL for Clonostachys sp, 4.6 U / mL for Penicillium sp., 6.9 U / mL for Beauveria brongniartii and 30.3 U / mL for Paecilomyces sp. The crude extract that showed greater activity was subjected to partial purification using ethanol (0-80%). Where there was no significant increase in purity. The fraction purified by organic solvent with the highest total enzymatic activity (5.688 U), was subjected to purification by Ion Exchange Chromatography on a DEAE-Cellulose column, with a flow of 1mL / min and a mobile phase of 0.1M Tris-HCl pH 8 , 0. The purified enzyme showed 35% yield and a purification rate of 16.08 times. After purification, the protease from Paecilomyces sp. was characterized in terms of class, optimal temperature, thermostability and enzymatic kinetics. Serine protease inhibitors from which no inhibition was observed were used, demonstrating that the protease produced does not belong to this class. The enzymatic activity was analyzed at different temperatures (25, 30, 35, 40, 45, 50, 55 and 60 ° C), showing greater activity at 50 ° C, for the crude extract and 35 ° C, for the purified enzyme. As for thermal stability, the protease of the crude extract, after being incubated at temperatures 25; 35; 40; and 45 ° C, demonstrated greater stability in the first 2h, at 45 ° C. The kinetic parameters were found experimentally, using different concentrations of azocasein - 0.1 to 3.0% (w / v) -, of which the values of Km = 0.142% and Vmax = 6.8 U / mL were seen. In view of the results obtained, it is concluded that the fungi used were capable of producing protease by submerged fermentation and that the skimmed milk medium is a potential substrate for the production of proteolytic enzymes.